IceCube – Interactive Exploration and Analysis of Icelandic Health Care Data Using OLAP - Einar Máni Friðriksson 1980- (2010)
Ritgerðin er lokuð til janúar 2014 For the last two decades the health care industry has increasingly tried to embrace new information technologies as well as software applications in its search for efficiency and higher quality of care. In Iceland, since 1997, information about patient data is recorded in Saga, an Icelandic electronic medical record system. The system is running at all major health care centres, hospitals and private practices in Iceland. This research uses the data from, according to the database specialist working on Saga, the biggest database in Iceland which is the health care database at Heilsugæsla Höfuðborgarsvæðisins (the health service in Reykjavik and its surroundings). The objective of this research is to describe the creation of IceCube, an OLAP cube which enables interactive exploration and analysis of public health care data. The research confirms that OLAP simplifies data analysis in the specified domain and offers the possibility of data mining the health care data and the application of pattern recognition and prediction of trends and behaviour. EMR - Heilbrigðislausnir